CCNG1 (Cyclin G1) regulation by mutant‐P53 via induction of Notch3 expression promotes high‐grade serous ovarian cancer (HGSOC) tumorigenesis and progression - Xu, Ying (Cancer Med, 2018)
TP53 mutation is considerably common in advanced high‐grade serous ovarian cancer (HGSOC) and significantly associated with a poor prognosis. In this study, we investigated the role of Cyclin G1 (CCNG1), a target gene of wild‐type TP53 (P53wt), in HGSOC and the possible regulatory mechanism between TP53 mutant (P53mt) and CCNG1 in the progression of HGSOC. High expression level of CCNG1 was found in 61.3% of HGSOC tissues and only 18.2% in fimbriae of fallopian tubes. Additionally, overexpression of CCNG1 was significantly associated with a shorter overall survival (P < 0.0001) and progression‐free survival (P < 0.0004) in HGSOC patients. In vitro, CCNG1 promoted both tumor cell motility by inducing epithelial‐mesenchymal transition (EMT) and resistance to cisplatin (CDDP). In vivo, knockdown expression of CCNG1 inhibited cancer metastasis. Furthermore, P53mt increased the expression of CCNG1 by regulating Notch3 expression, and a positive correlation between CCNG1 and Notch3 protein expression was observed by Immunohistochemistry (IHC) (r = 0.39, P: 0.01528). In conclusion, the activation of P53mt‐Notch3‐CCNG1 pathway was responsible for tumor progression to advanced disease with correlation with worse prognosis in patients with HGSOC. These data suggest a possible molecular mechanism of disease and highlights CCNG1’s potential role as a therapeutic target in HGSOC.